Characteristics and Outcomes of Patients Receiving Volatile Anesthetics in Near-Fatal Asthma: A Retrospective Observational Cohort Study - Christopher Remmington, MPharm; Luigi Camporota, MD, PhD; Daniel Taylor, MD; Angelo Sousa, BSc; Barnaby Sanderson, MSc; Guy Glover, MD (Critical Care Explorations)
IMPORTANCE AND OBJECTIVES:. Inhaled volatile anesthetics are employed as rescue therapy in near-fatal asthma, despite limited evidence. This study aims to describe the characteristics, management, and outcomes of mechanically ventilated adult patients with near-fatal asthma, stratified by the use of volatile anesthetic therapy. DESIGN:. Retrospective single-center observational cohort study. SETTING:. Tertiary critical care and extracorporeal membrane oxygenation (ECMO) unit. PARTICIPANTS:. Adults 16 years old or older receiving mechanical ventilation (MV) for greater than or equal to 24 hours and/or ECMO between January 2016 and August 2023 for near-fatal asthma. MAIN OUTCOMES AND MEASURES:. We recorded demographics, disease severity tidal volumes, and ventilator settings, by treatment over the first 100 hours. Outcomes were duration of ECMO and MV, ICU length of stay, 90-day mortality, and adverse drug reaction. RESULTS:. Sixty-two patients were included (62.9% female), with a median (interquartile range [IQR]) age of 45 years (29–51 yr). Median (IQR) pH 7.13 (6.93–7.23), Paco2 12.9 kPa (8.7–16.2 kPa), and tidal volume 178 mL (50–300 mL). Most patients received IV bronchodilators and 32 (51.6%) required ECMO. Thirty-eight patients (61.3%) were treated with volatile anesthetics. Volatile patients had worse ventilation and blood gas parameters before treatment, more barotrauma, and were more likely to be receiving ECMO. Despite this, improvements in tidal volume occurred in the volatile group (mean increase, 204 mL [83.9%]; 95% CI, 110–298; p < 0.001). Median (IQR) duration of MV and ICU length of stay in volatile and no volatile patients were 10 days (8–16 d) vs. 5 days (3–10 d; p = 0.001) and 15 days (13–20 d) vs. 9 days (7–14 d; p = 0.001), respectively. ICU and 90-day mortality in volatile and no volatile patients were 5.3% vs. 4.2%. CONCLUSIONS AND RELEVANCE:. The use of inhaled volatile anesthetics for near-fatal asthma, including during ECMO, appears to be feasible and safe, and with favorable clinical outcomes; however, no conclusions regarding efficacy can be directly inferred.